2020
DOI: 10.21203/rs.3.rs-45865/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complaints of Paediatric Patients After Dental Treatment Under General Anaesthesia I: Pain. A Prospective Observational Study.

Abstract: Background: Dental treatment under general anaesthesia for children is a useful option in behaviour management. However, this treatment modality may also be accompanied by considerable postoperative pain. We aimed to specify factors related to postoperative pain and those that alleviate complaints. Methods: Children treated in general anaesthesia and their parents voluntarily participated in the study. Pain was reported daily by children using Wong Baker FACES Pain Rating Scale and by caregivers, using a yes/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Our study revealed 78.3% of the children were eating a regular diet after 3 days and did not need any medications afterwards. El Batawi et al [ 39 ] explained that after dental rehabilitation under GA, children experienced no oral symptoms, healthy gums, and an elimination of problems when they tried to eat regular healthy food (in fact, any type of food).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed 78.3% of the children were eating a regular diet after 3 days and did not need any medications afterwards. El Batawi et al [ 39 ] explained that after dental rehabilitation under GA, children experienced no oral symptoms, healthy gums, and an elimination of problems when they tried to eat regular healthy food (in fact, any type of food).…”
Section: Discussionmentioning
confidence: 99%
“…A study mentioned in literature that we came across investigated similar objectives such as ours [ 39 ]. The study has several strengths, including its standardized GA protocol and inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%